ERRORS MADE BY THE TENTH GRADE STUDENTS OF SMA NEGERI 1 ULU MORO’O IN THEIR WRITING RECOUNT TEXT COMPOSITION IN ACADEMIC YEAR 2020/2021 - Gulo, Arif Santo; Sembiring, Novalina Prima; Pangaribuan, Jontra Jusat (Kairos English Language Teaching Journal, 2021)
This study is about errors made by the tenth grade students of SMA Negeri 1 Ulu Moroâ€™o in writing recount text composition in academic year 2019/2020. The objectives of this study is to find outÂ types of errors made by the tenth grade students in their writing recount text composition and to find out the most dominant errors made by the tenth grade students in writing recount text composition. The instrument of the research is test and documentation. The research methodology is descriptive qualitative. The subject of this study is the tenth grade students of SMA Negeri 1 Ulu Moroâ€™o, which is consist of 30 students. The result of this study showed that there are four types of errors that occur; they are error of omission, error of addition, error of misformation and error of misordering. The data was taken from the test: it was written text. The findings showed that errors made by the students were 19,80% omission, 17,82% addition, 53,46% misformation, and 8,91% misordering. The writer observed 101 total errors. From the frequency of each error types, misformation was the error which most frequently produced by the students. The writer concluded that misformation was the dominant kind of errors made by the tenth grade students of SMA Negeri 1 Ulu Moroâ€™o in writing recount text composition.